Circulating tumor cells in metastatic breast cancer patients treated with immune checkpoint inhibitors – a biomarker analysis of the ALICE and ICON trials - Nikolai Kragøe Andresen; Andreas Hagen Røssevold; Elin Borgen; Cecilie Bendigtsen Schirmer; Bjørnar Gilje; Øystein Garred; Jon Lømo; Marius Stensland; Oddmund Nordgård; Ragnhild Sørum Falk; Randi R. Mathiesen; Hege G. Russnes; et al. (Molecular Oncology)
Immune checkpoint inhibitors (ICIs) have been introduced in breast cancer (BC) treatment and better biomarkers are needed to predict benefit. Circulating tumor cells (CTCs) are prognostic in BC, but knowledge is limited on CTCs in the context of ICI therapy. In this study, serial sampling of CTCs (CellSearch system) was evaluated in 82 patients with metastatic BC enrolled in two randomized trials investigating ICI plus chemotherapy. Programmed death‐ligand 1 (PD‐L1) expression on CTCs was also measured. Patients with ≥ 2 CTCs per 7.5 mL at baseline had gene expression profiles in tumor suggestive of increased T‐cell activity, including increased tumor inflammation signature (TIS) in both triple‐negative (P = 0.010) and hormone receptor‐positive (P = 0.024) disease. Patients with luminal A BC had higher CTC levels. The association between CTC status and outcome was most apparent 4 weeks into therapy. PD‐L1 expression in CTCs was observed in 6/17 CTC‐positive patients and was associated with inferior survival. In conclusion, our study indicates that CTC numbers may inform on tumor immune composition, as well as prognosis. These findings suggest a potential of using CTCs as an accessible biomarker source in BC patients treated with immunotherapy.